Synthes and study of some 2(diphenylacetyl)indandion-1,3 compounds with alkaly metals - A. N. Kochetov; L. Yu. Alikberova; К. A. Shestakov (Тонкие химические технологии, 2006)
Some 2(diphenylacetyl)indandion-1,3 compounds with alkaly metals were synthesized and studied. Only Na and K derivatives have enough solubility for water-soluble ratycide compositions.